A study on film piracy among students in Malaysia / Syamimi Qurratu Aim Ismail, Nurwasilah Muhammad and Nurul Syazwani Mohd Sukri - Ismail, Syamimi Qurratu Aim; Muhammad, Nurwasilah; Mohd Sukri, Nurul Syazwani (2014)
In this study, the main objective of the writers has been to study the film piracy in Malaysia, especially its enforcements. To this degree, the writers hope that this study has at least been a partial success and may prompt a superior comprehension and enforcement of the film piracy by the authority. The general law concerning film piracy is the Copyright Act 1987 and the Optical Disc Act 2000. In spite of the fact that the procurements in these Acts has explicitly constitutes the law and liability that would be endured by the wrongdoer, the film piracy is as of now occurrence. Surely, the authors have been profited colossally from this study. The writers would like to take a chance to record their appreciation and thankfulness to the staff of the Malaysian Intellectual Property Organization (MylPO), not to overlook all other people who have helped in somehow sometime during this study.